Studies of the Effect of Storage Conditions on Some Pharmaceutical Parameters of Powders and Tablets (Dhaka University Journal of Pharmaceutical Sciences, 2016)
This study evaluates the effect of storage conditions on some pharmaceutical parameters of powders (paracetamol, corn starch, tragacanth and polyvinyl pyrrolidone) and tablets (paracetamol, metronidazole and vitamin C). For powdered samples, angle of repose, bulk and tapped densities were determined while the tablets were evaluated for hardness, friability and disintegration before and after exposure to various humidity conditions, radiations from telecommunication mast and sunlight at intervals of 24 hrs & 1, 2, 4 and 8 weeks. The results showed a decrease in the angle of repose for paracetamol, corn starch, polyvinyl pyrollidone and tragacanth powders on exposure to sunlight. There was no significant (p>0.05) change in the tapped and bulk densities under the different storage conditions over the storage period. No organoleptic changes were observed for any of the samples stored under the environmental conditions over the two-month period. All the tablets stored over the two- month period conformed to the official BP standard for weight uniformity. Paracetamol tablets exposed to 93% relative humidity (RH) showed significantly lower reduction (P